Cambios climáticos a escala orbital y milenaria en el Atlántico norte entre 800.000 y 400.000 años - Alonso García, Montserrat (2010)
[EN]From a climatic and oceanographic point of view, the North Atlantic is a very important area because the main sources of deep water formation, which drive thermohaline circulation, are in the Norwegian-Greenland Sea and the Labrador Sea. Hence, changes in North Atlantic circulation have a great impact on global circulation. In this Thesis a section of the North Atlantic sediment core IODP Site U1314 was studied. This core was recovered in a key area for studying North Atlantic current variations and IRD discharges as well as changes in the strength of the Atlantic Meridional Overturning circulation (AMOC). Several records were obtained from micropaleontological and geochemical analysis on foraminifers: stable oxygen and carbon isotopes from benthic foraminifers (mainly C. wuellerstorfi), stable oxygen and carbon isotopes from two planktic foraminifer species N. pachyderma sin y dex, IRD fluxes, planktic foraminifer assemblages and trace elements from the planktic foraminifer N. pachyderma sin. Additionally, time series analyses were performed on all the records above mentioned and on the records from the Antarctic ice core EDC. The first aim of this Thesis was establishing the chronological framework for the studied interval. We tuned our benthic δ18O with the Antarctic temperatures from EDC ice core. The studied interval encompasses from MIS 19 to 11, which means from 800 to 400 thousand years (ka) approximately. Using the paleoceanographic and paleoclimatic proxies above mentioned, we propose that glacial-interglacial cycles can be divided in five stages: 1) Early interglacial stage. During this stage the Arctic and Polar fronts were located in a position similar to their present day position. The AMOC was very active and the NAC reached the Norwegian-Greenland Sea and the Labrador Sea where it sank to generate deep waters, like it happens nowadays. 2) Late interglacial stage. During this stage the Arctic front started to migrate southeastwards reaching a position near Site U1314. However, the low benthic ...